2004
DOI: 10.1088/0953-4075/37/21/008
|View full text |Cite
|
Sign up to set email alerts
|

Classical and semi-classical treatments of Li3+, Ne10++H(1s) collisions

Abstract: We perform molecular close-coupling and impact-parameter classical trajectory Monte Carlo calculations of total and partial cross sections for capture and ionization in collisions of highly charged ions on H(1s). We first consider Li3++H(1s) as a benchmark to ascertain the complementarity of the methods, and then Ne10++H(1s), which has been scarcely studied up to now, and has recently become of interest for fusion plasma research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
48
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(64 citation statements)
references
References 53 publications
14
48
2
Order By: Relevance
“…For the lowest n levels shown in Fig. 8, the microcanonical CTMC partial cross sections agree with the semiclassical data, but, as the collision energy increases the microcanonical cross sections show an unphysical rapid fall as n increases, as it was found in previous works [29][30][31]33].…”
Section: Partial N-resolved Cross Sectionssupporting
confidence: 88%
See 3 more Smart Citations
“…For the lowest n levels shown in Fig. 8, the microcanonical CTMC partial cross sections agree with the semiclassical data, but, as the collision energy increases the microcanonical cross sections show an unphysical rapid fall as n increases, as it was found in previous works [29][30][31]33].…”
Section: Partial N-resolved Cross Sectionssupporting
confidence: 88%
“…Similar comparisons for H(n=1) can be found in reference [29]. Previous calculations on Li 3+ , B 5+ and Ne 10+ + H collisions [30,29,33] showed that the hydrogenic-CTMC treatment provides accurate ionization and total and n-resolved electron capture cross sections for n n max , where n max is the most populated level of the ion A (q−1)+ formed in the CX reaction. The microcanonical-CTMC treatment leads in general to more accurate CX cross sections into low-lying states, as explained in detail in [29].…”
Section: Theoretical Methodssupporting
confidence: 68%
See 2 more Smart Citations
“…In the high-speed regime (v ∼ v 0 ), the collision dynamics become more important for the capture process, and the peak population level is gradually smeared out among several adjacent shells. We compiled the velocity-dependent, n-resolved cross sections for reactions involving Be, B, C, N, O, Ne, and Fe ions from theoretical calculations (Ryufuku 1982;Shipsey et al 1983;Fritsch & Lin et al 1984;Belkić et al 1992;Toshima & Tawara 1995;Harel et al 1998;Raković et al 2001;Errea et al 2004;Nolte et al 2012;Wu et al 2011Wu et al , 2012Mullen et al 2015). As shown in Fig.…”
Section: N-shell Populationsmentioning
confidence: 99%